Arthur Miller’s A View from the Bridge as Cognitive Ethical Narrative - Hossein Pirnajmuddin; Omid Amani (European Journal of American Studies)
This article sheds some light on ethical issues in Arthur Miller’s A View from the Bridge from the cognitive poetic perspective, especially Marie-Laure Ryan’s theoretical framework of the Possible Worlds Theory. It is argued that Miller’s play could be considered as cognitive ethical narrative as it highlights ethical considerations (centrally, issues of right and wrong, value and choice) in relation to the cognitive valences of the characters as well as those of the readers (who are steered to imaginatively apprehend the possibility that narrative actions and values may occur in the real world). As such, viewing the play through the lens of cognitive poetics can illustrate its ethical affordances, particularly with respect to the issue of choices, which ultimately endow human life with meaning. Adding some reflections on the philosophical implications of Sartre and Levinas, it is proposed that the protagonist’s act of betrayal is circumstantially complex. The conflict of values it involves could be illuminated through the consideration of the conflicting anguished W-world/Social O-world of the protagonist and the Communal O-world/hospitable W-world of the community in which he lives.